Swing time ebook A novel. - Smith, Zadie (2016)
“Smith’s thrilling cultural insights never overshadow the wholeness of her characters, who are so keenly observed that one feels witness to their lives.”  —O, The Oprah Magazine “A sweeping meditation on art, race, and identity that may be [Smith’s] most ambitious work yet.” — Esquire A New York Times bestseller • Finalist for the National Book Critics Circle Award for Fiction • Longlisted for the Man Booker Prize An ambitious, exuberant new novel moving from North West London to West Africa, from the multi-award-winning author of White Teeth and On Beauty . Two brown girls dream of being dancers—but only one, Tracey, has talent. The other has ideas: about rhythm and time, about black bodies and black music, what constitutes a tribe, or makes a person truly free. It's a close but complicated childhood friendship that ends abruptly in their early twenties, never to be revisited, but never quite forgotten, either. Tracey makes it to the chorus line but struggles with adult life, while her friend leaves the old neighborhood behind, traveling the world as an assistant to a famous singer, Aimee, observing close up how the one percent live. But when Aimee develops grand philanthropic ambitions, the story moves from London to West Africa, where diaspora tourists travel back in time to find their roots, young men risk their lives to escape into a different future, the women dance just like Tracey—the same twists, the same shakes—and the origins of a profound inequality are not a matter of distant history, but a present dance to the music of time. Zadie Smith's newest book, Grand Union , published in 2019.